Open and Distance Education in Asia, Africa and the Middle East National Perspectives in a Digital Age - Zawacki-Richter, Olaf; Qayyum, Adnan (SpringerBriefs in Education, 2019)
This book is open access under a CC BY 4.0 license. This book describes the history, structure and institutions of open and distance education in six countries: China, India, Russia, Turkey, South Africa and South Korea. It describes how open and distance education is evolving in a digital age to reflect the needs and circumstances of the national higher education systems in these countries. It also explores the similarities and differences between how their open and distance higher education systems are managed and structured. This book is the second in a series, following Open and Distance Education in Australia, Europe and the Americas (Springer 2018). Both books compare and draw conclusions about the nature of open and distance education in the context of various national higher education systems. In a digital era characterized by the growing use of online, open and distance education, this book will prove particularly valuable for policy-makers and senior administrators who want to learn about establishing or expanding open and distance education services. In addition, it offers a valuable reference guide for researchers, academics and students interested in understanding the different approaches to open and distance education.